Machinability Assessment Of 3D-Printed CoCrMo Plate : Influence Of Micro-drill Bit Designs - Mohd Affifudin, Abdul Patar; Mohd Azlan, Suhaimi; Safian, Sharif; Denni, Kurniawan; Amrifan S., Mohruni; Zhuang, Kejia (Tamkang University Press, 2024)
Cobalt chromium molybdenum (CoCrMo) is a hard-to-cut material widely utilized in the fields of medical, biotechnology, and aerospace engineering due to its exceptional combination of properties, including high strength, toughness, wear resistance, and low thermal conductivity. However, some of these attributes of CoCrMo often pose obstacles to its machinability, leading to rapid tool wear and a shortened tool life. Therefore, this paper investigates the impact of different micro drill tool designs (denoted as S and EZ by the manufacturer) with alteration to its point angles with constant machining parameters on the forces and wear when micro drilling CoCrMo. Three-dimensional (3D) printed CoCrMo plates are fabricated using the Selective Laser Sintering (SLS) process, and custom design tool bits with preferred geometries are also prepared. Output forces are measured using a dynamometer, while wear is assessed through optical microscopy. EZ design tool outperforms the S-design tool due to the significantly lower magnitude of thrust forces of 131.86 N at 118◦ point angle it generates. While S type tool design at the same angle produces 508.72 N thrust force output. Lower forces are anticipated to result in a reduced wear rate for the tool, potentially extending its lifespan. The lowest wear rate was by EZ type tool at 118◦ with only 0.122 m while S type tool at the same has a maximum average wear of 0.231 . The relationship between forces and wear are directly proportional.